2021
DOI: 10.1021/acs.jproteome.1c00189
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Signature of Urosepsis: From Discovery in a Rabbit Model to Validation in Humans

Abstract: Urosepsis after upper urinary tract endoscopic lithotripsy (UUTEL) may cause uroseptic shock with high mortality, which can be prevented if early diagnosis and timely intervention are implemented with help of a diagnostic protein panel. The plasma of five rabbits of uroseptic shock and five controls was subjected to exploratory proteomics to search biomarker candidates from proteomic profiles related to uroseptic shock. Then, plasma from 21 nonsepsis and 20 urosepsis patients according to European diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, widely applied and standardized animal models of urosepsis are relatively rare. Some scholars have found that rabbits can be used to develop models of urosepsis by injecting E. coli into the renal pelvis (13)(14)(15)(16). Rodents, the most widely used for experimental research, are rarely used to make models of urosepsis.…”
Section: Introductionmentioning
confidence: 99%
“…However, widely applied and standardized animal models of urosepsis are relatively rare. Some scholars have found that rabbits can be used to develop models of urosepsis by injecting E. coli into the renal pelvis (13)(14)(15)(16). Rodents, the most widely used for experimental research, are rarely used to make models of urosepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular changes associated with sepsis survival from patients with primary UTIs are not known. A prior proteomic study in UTI models and patients who developed sepsis proposed lipopolysaccharide-binding protein, clusterin, and VCAM1 as diagnostic markers of sepsis (52). Others have identified differentially expressed proteins involved in coagulation, the acute phase response, lipid homeostasis, and iron ion transport as associated with sepsis severity (53).…”
Section: Discussionmentioning
confidence: 99%
“…These changes are consistent with others’ reports of sepsis survival and disease severity of UTIs via discovery and targeted LC-MS/MS, enzyme-linked immunosorbent assays, real-time reverse transcription polymerase chain reaction, and western blotting (54–61). Similar to our previous analysis of patients with primary intra-abdominal infection, proteins related to inflammation and hepatic fibrosis/hepatic stellate cell activation were decreased in sepsis survivors (39), including VCAM1, which has also been proposed as a diagnostic biomarker for sepsis secondary to UTIs (52). Therefore, these pathways and related molecules may be key factors involved in sepsis survival across primary infection sources, especially soluble forms of proteins like VCAM1.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there exists a discernible scarcity of widely employed and standardized animal models pertaining to urosepsis. Certain scholars revealed that a urosepsis model can be established via intrarenal infusion of Escherichia coli into New Zealand rabbits' renal pelvis [ 8 , 9 ]. Recently, some scholars have attested to the efficacy of the Wistar rat model for urosepsis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, for New Zealand rabbits or Wistar rats, due to the absence of specific antibodies or transgenic animals, subsequent foundational mechanistic studies are impeded. Consequently, only physiological explorations can be conducted at present [ 9 ]. Given mice's widespread use as model organisms in experimental research, a standardized mouse model of urosepsis would facilitate swift exploration of urosepsis' pathophysiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%